Flow of Eyring-Powell hybrid nanofluid on a shrinking cylinder with joule heating and viscous dissipation - Waini, Iskandar; Khan, Umair; Zaib, Aurang; Ishak, Anuar; Pop, Ioan (Pushpa Publishing House, 2024)
This paper deals with the AA7075-AA7072/methanol hybrid nanofluid flow incorporated with the Eyring-Powell model. The fluid flows over a shrinking cylinder subject to magnetohydrodynamic (MHD), Joule heating, and viscous dissipation. The governing equations are transformed into similarity equations by employing suitable similarity transformations. Then, MATLAB software is used to program the code with the aid of the bvp4c function. The findings prove that the dual solutions are generated for a certain domain of shrinking parameters. Besides, higher values of heat transfer and skin friction are obtained by the imposition of the magnetic and Eyring- Powell fluid parameters. However, the heat transfer is reduced in the presence of viscous dissipation with a higher Eckert number.